Seroprevalence of human toxocariasis in Latin America and the Caribbean: a systematic review and meta-analysis - Ulloque-Badaracco, Juan R.; Hernandez-Bustamante, Enrique A.; Alarcón-Braga, Esteban A.; Huayta-Cortez, Miguel; Carballo-Tello, Ximena L.; Seminario-Amez, Rosa A.; Rodríguez-Torres, Alejandra; Casas-Patiño, Donovan; Herrera-Añazco, Percy; Benites-Zapata, Vicente A. (Frontiers in Public Health, 2023)
Our objective was to carry out a quantitative synthesis of the seroprevalence of human toxocariasis in Latin America and the Caribbean.A systematic research was carried out in six electronic databases using a research strategy that combined MeSH terms with free terms. The selection of the articles and the extraction of information were carried out in a double and independent manner. The Newcastle-Ottawa tool was used to assess the risk of bias in the included articles. The meta-analysis used the random-effects approach and subgroup analysis and sensitivity for risk of bias were performed. We included 101 articles with a total of 31123 participants. The studies were conducted between 1990 and 2022 with Brazil contributing the largest number of studies (n=37). The overall seroprevalence of human toxocariasis was 31.0% (95% CI: 27.0%-35.0%, I2=99%). The seroprevalence of ocular toxocariasis was similar to the overall seroprevalence while participants who had dogs at home was notably higher, 68.0% (95% CI: 61.0%-75.0%, I2=96.15%). In addition, there was a lower seroprevalence in studies where only adults were included compared to children or mixed. In contrast, no differences were found between seroprevalences in studies conducted in the community compared to the hospital. The overall seroprevalence of human toxocariasis in Latin America and the Caribbean is high. We found that seroprevalence is higher when a dog is kept at home. In contrast, seroprevalence is lower in studies conducted only in adults. Our findings can be used to establish epidemiological surveillance strategies for the prevention and early identification of this pathology.